The Practice of Heutagogy, Peeragogy and Cybergogy Approach among Vocational College Instructors - Mohamad Anuar, Mohamad Adham; Ming Foong, Lee; Andika Bagus Nur Rahma Putra, (Journal of Technical Education and Training, 2024)
This study investigates the implementation levels of Heutagogy, Peeragogy, and Cybergogy approaches among instructors at vocational colleges in Malaysia. Employing a quantitative survey research design, data were collected from a sample of 241 instructors across 15 vocational colleges, representing various Technology fields such as Automotive, Electrical, Electronic, Construction, Welding, Industrial Machining, Refrigeration & Air Conditioning, and Computer Systems & Network Technology. The sample was selected using a cluster stratified convenient sampling method. Demographic information, including gender, age, race, institutional zone, vocational college, program, experience, qualification, certificate, and class, was gathered. A structured questionnaire comprising 53 items served as the primary data collection instrument. Data analysis was conducted using SPSS software to derive frequency values, percentages, mean scores, and standard deviations. The Kruskal-Wallis and Mann-Whitney U tests were employed to identify differences in the implementation of Heutagogy, Peeragogy, and Cybergogy approaches among the instructors. The findings indicate a high level of implementation for Heutagogy and Peeragogy approaches, while the Cybergogy approach is practiced at a moderate level. Significant differences were observed in the implementation of these approaches based on the instructors’ fields and teaching experience. To enhance the practice of Cybergogy, it is recommended that vocational college administrations provide training workshops or courses to improve the teaching skills of their academic staff for 21st century learning environment.